1996
DOI: 10.1159/000227588
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Pulmonary Metastasis from Uterine Cancer

Abstract: Background: Endometrial cancer is the most common female genital cancer and approximately 90% of the cases are diagnosed while they are still confined to the uterus. However, the frequency and the pattern of pulmonary metastasis (PM) have not been studied systematically. Patients and Methods: From 1962 to 1989, 90 patients wit PM were identified by computerized search of the medical records of the 1,550 (5.8%) patients admitted to the Massachusetts General Hospital with the diagnosis of uterine cancer. The med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 7 publications
1
31
0
Order By: Relevance
“…In a study by Bouros et al (51), only 6 of the 90 patients who had pulmonary metastasis manifested a pleural effusion. Of those patients, 50% had concurrent parenchymal disease.…”
Section: Thoracic Manifestations Of Endometrial Malignancies In This mentioning
confidence: 93%
See 4 more Smart Citations
“…In a study by Bouros et al (51), only 6 of the 90 patients who had pulmonary metastasis manifested a pleural effusion. Of those patients, 50% had concurrent parenchymal disease.…”
Section: Thoracic Manifestations Of Endometrial Malignancies In This mentioning
confidence: 93%
“…Bouros et al (51) have reported that up to 34% of patients presented with pulmonary metastasis as the only site of recurrence. As seen in other malignancies, the autopsy-based rate of pulmonary metastasis is much higher documented by Turner et al (50).…”
Section: Thoracic Manifestations Of Endometrial Malignancies In This mentioning
confidence: 99%
See 3 more Smart Citations